Analysis of Students’ Literacy Skills in Identifying Religious Intrinsic Elements in the Folktales Puyang Lambung Karang and Bujang Juaro among Fifth-Grade Learners at SDN 1 Tanjung Sakti, Lahat Regency - Rega Agustina (Journal of Primary Education (JPE), 2026)
This study aims to analyze the literacy abilities of elementary school students in identifying intrinsic elements with religious nuances in the folktales Puyang Lambung Karang and Bujang Juaro. The research is grounded in the importance of literacy as a multidimensional competence encompassing the ability to comprehend, interpret, and analyze texts, as well as the relevance of folktales as a medium for fostering religious and cultural character education. Using a descriptive qualitative approach, the study was conducted at SDN 1 Tanjung Sakti from February to March 2025 and employed observation, interviews, and documentation as data sources. Data validity was ensured through source, method, and document triangulation.The findings indicate that students’ literacy abilities in identifying themes, characters, plot, setting, and moral messages are still categorized as developing. Some students were able to connect intrinsic elements with moral and religious values—such as honesty, mutual assistance, and the prohibition of immoral behavior—while others demonstrated only literal comprehension without deeper interpretation. Variations in student performance were influenced by internal factors, including reading interest, motivation, and limited vocabulary, as well as external factors such as the predominance of lecture-based instruction, a lack of learning media, and suboptimal learning environment support. These results are interpreted through Piaget’s cognitive developmental theory and Vygotsky’s social constructivism, both of which emphasize the importance of concrete experiences, social interaction, and teacher scaffolding in enhancing literacy comprehension and moral understanding. The study recommends the use of interactive and contextual learning strategies based on local folktales to strengthen students’ cultural and religious literacy.